Host Iron Nutritional Immunity Induced by a Live Yersinia pestis Vaccine Strain Is Associated with Immediate Protection against Plague - Zauberman, Ayelet; Vagima, Yaron; Tidhar, Avital; Aftalion, Moshe; Gur, David; Rotem, Shahar; Chitlaru, Theodor; Levy, Yinon; Mamroud, Emanuelle (Frontiers in Cellular and Infection Microbiology, 2017)
Prompt and effective elicitation of protective immunity is highly relevant for cases of rapidly deteriorating fatal diseases, such as plague, which is caused by Yersinia pestis. Here, we assessed the potential of a live vaccine to induce rapid protection against this infection. We demonstrated that the Y. pestis EV76 live vaccine protected mice against an immediate lethal challenge, limiting the multiplication of the virulent pathogen and its dissemination into circulation. Ex vivo analysis of Y. pestis growth in serum derived from EV76-immunized mice revealed that an antibacterial activity was produced rapidly. This activity was mediated by the host heme- and iron-binding proteins hemopexin and transferrin, and it occurred in strong correlation with the kinetics of hemopexin induction in vivo. We suggest a new concept in which a live vaccine is capable of rapidly inducing iron nutritional immunity, thus limiting the propagation of pathogens. This concept could be exploited to design novel therapeutic interventions.